Characteristics of Diamond-Like Carbon Coating Using Plasma Assisted Chemical Vapor Deposition on Steel Tool - Saifudin Saifudin; Wawan Purwanto; Jerry Chih Tsong Su (Automotive Experiences, 2020)
High Speed Steel (HSS) tool is commonly used in engineering applications, especially as cutters. The shortfall of this materials are wear and corrosion. However, these can be reduced by coating the surface of the material. Therefore, the purpose of this research is to investigate the effects of Diamond Like Carbon (DLC) coating, quenching heating treatment, and tempering on the physical and mechanical properties of HSS surface. The physical characteristics which will be investigated is the micro structure, while the mechanical characteristics are hardness, wear and corrosion rate. HSS has variations in their chemical composition (% mass): 0.75”“1.5 C, Co >12, V > 5, 4”“4.5 Cr,10”“20 W and Mo. Furthermore, DLC coating uses Plasma Assisted Chemical Vapor Deposition (PACVD) technique with variation in the duration of coating (1,2,3,4,5 and 6 hours) at temperature of 300â„ƒ, with pressure variations of 1.0, 1.2, 1.4, 1.6, 1.8 and 2.0 millibar. DLC coating material be treated from methane or ethane gas, which is streamed into the fire with Argon (Ar). The result shows variations in DLC coating and the hardness grade depends on the coating time and pressure variation. DLC coating for a duration of 4 hours under 1.8 mbar pressure can reduce the surface hardness of HSS tool by 62% accompanied by increased ductility.